1965
DOI: 10.1177/002216786500500103
|View full text |Cite
|
Sign up to set email alerts
|

A Note on the Peak Experience as a Personal Myth

Abstract: ONE of the most difficult problems for psychology is the fact that the psychologist must regard himself as a participant in the process which he is studying. He is both object and subject. There are, therefore, two complementary psychologies, the heirs of physical science and philosophy, reflecting this double viewpoint. One of the principal values of Maslow's recent focus of attention upon the peak experience is that aspect of psychology that attempts to point the way to wisdom for the subjectfor a humanity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The memory revives, in part, the original experience. It is somewhat like Warmoth's (1965) description of the peak experience as a personal myth. For instance:…”
Section: Effects Attributed To Aesthetic Peak Experiencesmentioning
confidence: 98%
“…The memory revives, in part, the original experience. It is somewhat like Warmoth's (1965) description of the peak experience as a personal myth. For instance:…”
Section: Effects Attributed To Aesthetic Peak Experiencesmentioning
confidence: 98%
“…Long ignored by modern scholars (Franco, Blau, & Zimbardo, 2011), the phenomenon of heroism is finally attracting the serious attention of scientists from multiple disciplines, especially psychology (Allison, Goethals, & Kramer, 2017). The mythic views of heroism examined by Joseph Campbell (1949) resonated with the general public, and also influenced humanistic and existential psychology during the peak of the Third Force movement in psychology through the incorporation of mythic and personal narrative in psychotherapy, research, and philosophical inquiry (see, e.g., Feinstein, Krippner, & Granger, 1988;Warmoth, 1965;Washburn, 1990). Starting in the early 1980s, APA Society for Humanistic Psychology's (SHP) former Division President, Frank Farley, suggested that small acts of everyday heroism also deserved attention and study (Farley, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Jung (1961) began his autobiography by writing, "I have undertaken, in my eighty-third year, to tell my personal myth" (p. 3). Arthur Warmoth (1965) wrote about the way certain memorable events may become personal myths, fulfilling on a personal level functions that cultural myths have historically performed for entire societies. In 1973, Rollo May remarked that the "underlying function of psychotherapy is the indirect reinterpretation and remolding of the patient's symbols and myths" (p. 342) and in 1975he added, "The individual must define his or her own values according to personal myths... [because] authentic values for a given patient emerge out of the personal myth ofthat patient" According to May (1975), psychotherapy can best be described as the collaboration between therapist and patient in the adventure of exploring the patient's awareness of himself or herself and others. '…”
Section: Observedmentioning
confidence: 99%